SEKTOR EKONOMI UNGGULAN KABUPATEN LOMBOK TENGAH - Muhammad Zainuri (Badan Perencanaan Pembangunan Daerah, Penelitian dan Pengembangan Kabupaten Sragen, 2021)
Lombok Tengah Regency has the potential to accelerate economic growth in the future along with the presence of the Mandalika Special Economic Zone (SEZ). This study aims to determine the leading economic sectors of Lombok Tengah Regency and explain the relationship between these leading economic sectors and the tourism activities. Based on the overlay analysis that combines shift share analysis and location quotient analysis, it is found that of the 17 existing economic sectors, all of them are included in the leading sector as many as 9 sectors and potential sector categories as many as 8 sectors. The transportation and warehousing sector and the accommodation and food and beverage provision sector which are closely related to tourism activities are not yet among the leading sectors, so they need to be improved in the future. Leading economic sectors such as agriculture, forestry and fisheries sector; manufacturing industry sector; and the services sector can take advantage of the presence of the Mandalika Special Economic Zone (SEZ) to increase demand. Further research can use Input Output Table Analysis to determine the interrelationship between economic sectors and to know the impact of improving an economic sector on the performance of the economy in general.